ID: 91. Issue 1 (November 2015) - Kimura, Akihiko; Ishida, Yuko; Nosaka, Mizuho; Kuninaka, Yumi; Mukaida, Naofumi; Kondo, Toshikazu
<x xml:space="preserve">Abstract</x> Introduction: Mechanical stress-induced chronic hypertension can initiate the development of cardiac hypertrophy and, ultimately, congestive heart failure. It is widely accepted that various chemokines are expressed in the heart in response to pressure overload. These chemokines might be involved in the cardiac remodeling and pathogenesis of heart failure. In this study, we investigated the roles of CCR5 in pressure overload-induced cardiac hypertrophy and heart failure in mice. Methods: Male C57BL/6J (WT) and CCR5-deficient (CCR5-KO) mice were subjected to transverse aortic constriction (TAC). Aortic constriction was achieved by tying around the transverse thoracic aorta against a 27-gauge needle using a 7–0 silk suture, and then removing the needle. Cardiac hypertrophy, fibrosis, cardiac function by echocardiography and expression of hypertrophy related molecules were examined. Results and discussion: Three weeks after TAC, CCR-5-KO mice exhibited more significant loss of cardiac function with cardiac hypertrophy, compared with WT mice, indicating that CCR5 plays a protective role in TAC-induced cardiac hypertrophy and heart failure. In WT mice, intracardiac Ccr5 expression was increased at 3 day and 1 week TAC, and CCR5 protein was expressed in the cardiac fibroblasts. Mechanical stress-induced inflammation is known to be indispensable for compensatory hypertrophy, however, which was significantly attenuated in CCR5-KO mice, compared with WT mice. Consistently, CCR5-KO mice lacked the initial compensatory hypertrophy. The lack of initial compensatory cardiac hypertrophy might lead CCR5-KO mice to pathological cardiac hypertrophy. Enhanced CCR5 expression in intracardiac fibroblasts might be crucially involved in the compensatory hypertrophy-induced by mechanical stress.